Pengolahan Ikan Asap Berdasarkan Konsep Cara Pengolahan Pangan yang Baik (CPPB) untuk Meningkatkan Branding Kuliner Unggulan Pantai Prigi Trenggalek - Rifqie Mariana, Rina; Wahyu Hidayat, Nur; Andoko, Andoko; Ade Lose Hermanto, Yon; Syah Pahlevi, Andreas; Muntholib , Muntholib (LPkM Universitas Bakrie, 2023)
Currently smoked fish is known as the superior cuisine of Prigi Beach, Trenggalek Regency. The local government in Trenggalek Regency was quite successful in empowering the community around Prigi Beach through training in producing smoked fish while at the same time utilizing abundant fish resources. However, their production and marketing processes were still conventional that which negatively impacted the profit since the products were deteriorated before they were all sold due to the limited targeted consumers that were Prigi Beach tourists. This community service offered solutions and methods such as counseling and practices regarding healthy, preserved, and safe storage for smoked fish process based on the Good Manufacturing Practices (GMP), and digital marketing training continued with gifting packing and freezer tools to one group of artisans. This activity was joined by 20 artisans in Tasikmadu Village, Prigi Bay, Watulimo District, Trenggalek Regency. After one month of monitoring and guidance by the community service team, artisans could improve their products into healthy, preserved, and safe products. Also, their market is widened not only limited to the beach, but also through Instagram and other social media. Thus, their profit gradually increased since August.